Poor HIV-Related Outcomes in Older Adults Newly Diagnosed With HIV: A 4-Year Retrospective Analysis From a Single Site in Asia. (1st May 2023) - Wong, Hoi Yee; Wong, Pui Li; Bador, Maria Kahar; Chong, Meng Li; Shenoi, Sheela; Rozanova, Julia; Syed Omar, Sharifah Faridah; Neelamegam, Malinee; Lee, Yew Kong; Rajasuriar, Reena
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: In resource-limited settings, HIV-related services are often targeted to younger key populations, although increasing reports have found that adults ≥50 years now account for among the highest increase in new HIV diagnosis. We assessed the proportion of new HIV infections among older adults (≥50 years) and compared their sociodemographics, risk behaviors, and HIV-related outcomes to newly diagnosed younger adults (<50 years). Methods: This retrospective analysis included all new HIV diagnosis from 2016 to 2019 at the University of Malaya Medical Centre, Malaysia. Trends of HIV diagnosis was assessed using join point regression analysis, and characteristics between the older and younger adults were compared using χ 2 test or Mann–Whitney U test. Kaplan–Meier analysis and log-rank test were used to compare the survival probability in both age groups. Results: From a total of 594 new HIV diagnosis between 2016 and 2019, 11.5% (N = 68) were among older adults with an annual percent increase of 5.50%. Older adults were more likely ethnic Indians ( P < 0.001), acquired HIV through heterosexual contact ( P = 0.001), had late presentation to care ( P = 0.003), and multimorbidity ( P < 0.001). Immunological responses after 12 months on antiretroviral therapy were comparable in both the groups. Older adults had a higher probability of death compared with younger adults (adjusted hazard ratio 1.81, 95% confidence interval: 1.02 to 3.23, P = 0.043) after adjusting for sex, mode of HIV transmission, late presentation to care, antiretroviral therapy initiation, and multimorbidity. Conclusion: Older adults diagnosed with HIV were associated with late care presentation and increased mortality. There is an urgent need to enhance uptake of HIV testing and linkage to care among older individuals in our setting.